The trustee's legal companion - Hanks, Liza, 1961-; Buckley, Shaila; Elias Zolla, Carol, 1971- (Nolo, 2026)
The Trustee's Legal Companion is a practical guide to administering a living trust. Intended for individuals serving as trustees, the book explains the responsibilities associated with trust management and provides step-by-step guidance on carrying out fiduciary duties. Topics addressed include evaluating whether to accept the role of trustee, managing and investing trust assets, administering ongoing trusts for spouses or other beneficiaries, working with professional advisors, handling tax matters, preparing accountings, communicating with beneficiaries, and distributing trust property. The work is designed to assist trustees in organizing and fulfilling their legal and financial responsibilities.